2015
DOI: 10.3892/etm.2015.2409
|View full text |Cite
|
Sign up to set email alerts
|

Expression of signal transducer and activator of transcription 3 and its phosphorylated form is significantly upregulated in patients with papillary thyroid cancer

Abstract: The aim of the present study was to investigate the expression of signal transducer and activator of transcription 3 (STAT3) and phosphorylated STAT3 (pSTAT3) in tissues of papillary thyroid cancer (PTC) in comparison with the expression in adjacent normal tissues. The expression of STAT3, pSTAT3, fibroblast growth factor 2 (FGF2) and vascular endothelial growth factor-C (VEGF-C) was examined in tissues of 42 cases of PTC and the adjacent normal tissues of 20 of the 42 PTC cases using immunohistochemistry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…A number of reports have revealed that the cytokine-induced activation of STAT3 is associated with the evasion of apoptosis, among other cancer hallmarks [6][7][8]. There is a strong correlation between STAT3 overexpression and the pathogenesis of thyroid cancer, as the dysregulated activation of STAT3 has been reported in human specimens of thyroid cancers [9,10]. Apoptosis, or programmed cell death is an important phenomenon that maintains normal cell proliferation and growth (regulated by a system of interconnected signals that is often dysregulated in most human pathologies, including cancer) [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports have revealed that the cytokine-induced activation of STAT3 is associated with the evasion of apoptosis, among other cancer hallmarks [6][7][8]. There is a strong correlation between STAT3 overexpression and the pathogenesis of thyroid cancer, as the dysregulated activation of STAT3 has been reported in human specimens of thyroid cancers [9,10]. Apoptosis, or programmed cell death is an important phenomenon that maintains normal cell proliferation and growth (regulated by a system of interconnected signals that is often dysregulated in most human pathologies, including cancer) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a number of reports have also revealed that the cytokine-induced activation of STAT3 is associated with the evasion of apoptosis, among other cancer hallmarks [6][7][8]. There is a strong correlation between STAT3 overexpression and the pathogenesis of thyroid cancer, as the dysregulated activation of STAT3 has been reported in human specimens of thyroid cancers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of STAT3 leads to the upregulation of MMP2 and VEGFA, thereby enhancing the migration and invasion of tumor cells (36). STAT3 is constitutively activated in numerous types of human cancer, usually by phosphorylation of a conserved tyrosine residue in response to extracellular signals from cytokines and growth factors (45). Activated p-STAT3 forms homo-or heterodimers that translocate into the nucleus and induce the transcription of target genes, including MMP2 and VEGFA.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that activated STAT3 participates in angiogenesis regulation, with a critical role 67 . VEGF and bFGF are known to be involved in endothelial cell proliferation, extracellular matrix degradation, endothelial cell migration, and modulation of junctional adhesion molecules; both have been described as the leading mediators of angiogenesis that can be upregulated by activated STAT3 in glioblastoma stem cells 68 , papillary thyroid cancer 69 , and colorectal cancer 70 , thereby promoting the formation of new blood vessels and development of cancer. STAT3 is involved in various aspects of tumor microenvironment to cultivate a favorable environment for cancer development.…”
Section: Pivotal Biological Functions Of Stat3 In Cancermentioning
confidence: 99%